Luteal tissue blood flow and side effects of horse-recommended luteolytic doses of dinoprost and cloprostenol in donkeys - Magalhaes, Humberto B. [UNESP]; Dell'Aqua, Jose Antonio [UNESP]; Canisso, Igor F. (Elsevier, 2024)
This study assessed luteolysis and side effects in jennies receiving standard horse-recommended doses of cloprostenol and dinoprost. Sixteen cycles of eight jennies were randomly assigned in a sequential crossover design to receive dinoprost (5 mg, i.m.) and cloprostenol (0.25 mg, i.m.) at 5-d post-ovulation. B-mode and Doppler ultrasonography were employed to assess luteal tissue size and blood flow before (-15 min and 0h) and after (0.5, 1, 2, 3, 4, 5, 6, 7, 8, 12, 24, and 48h) administering PGF2α. Immunoreactive progesterone concentrations were assayed at similar timepoints via RIA. Side effects such as sweating, abdominal discomfort, and diarrhea were scored at 15-min-intervals for 1h after PGF2α. Data normality was assessed with the Shapiro-Wilk's test. Luteal tissue size and blood flow were analyzed using PROC-MIXED and post-hoc by Tukey. Non-parametric tests analyzed side effect variables. The luteal blood flow increased overtime by 27% at 45 min and peaked by 49% at 3 h for dinoprost, and conversely, it increased by 14% at 30 min and peaked at 39% at 5h for cloprostenol (P<0.05). Luteal blood flow was reduced by 50%, 25%, and 10% on both groups at 8, 12, and 24h (P<0.05). Immunoreactive progesterone concentrations decreased in 0.5h for dinoprost and 1h for cloprostenol and gradually decreased by 48h (P<0.05). Dinoprost induced greater sudoresis scores, while cloprostenol resulted in greater abdominal discomfort and diarrhea scores (P<0.05). In conclusion, dinoprost and cloprostenol effectively induced luteolysis with distinct side effects; this could guide practitioners’ case selection to use one or another PGF2α.
Keywords: Corpus luteum; Doppler ultrasonography; Jennies; Progesterone